Semantic verbal fluency in Spanish-speaking people: a comparative analysis - Ramírez, M; Ostrosky-Solís, F; Fernández, A; Ardila-Ardila, A (Revista de neurologiá, 2005)
Semantic verbal fluency (SVF) is the most commonly used test in the evaluation of normal and pathological functioning, whether it be clinically or experimentally. Several studies have suggested that the age, schooling and culture of the subject all affect performance in this test. To date no research has been conducted that proves whether there are differences between subjects who speak the same language but who come from different countries. Data from the 'animals' category of the SVF in adult Spanish-speaking subjects and also the influence exerted by culture, age and schooling on the outcomes in this test were both submitted to analysis. The aforementioned variables were compared with the data reported by five research groups. The SVF test yields similar data from one Spanish-speaking country to another, provided that the subjects' age and schooling are taken into account. The differences found in this study may be due to variations in the way the tests are administered and scored rather than any cultural effect. We propose a standardised method of applying the test, so as to allow these variables to be unified in the future. Age and schooling are factors that determine performance in the SVF, although this is not true of culture.